EVALUASI IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN KEFARMASIAN DI PUSKESMAS WILAYAH PERIFER KOTA SAMARINDA - Abdissalam, Erfan; Rahman, Fikri Difa Auliyah; Hanifa, Deasy Nur Chairin; Ghozali, Muhammad Thesa; Susanto, Yugo (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Pharmaceutical services in Community Health Centers play an essential role in ensuring rational drug use and quality of health services. The government has set standards for pharmaceutical services through Ministerial Regulation No. 74 of 2016 and Ministerial Regulation No. 26 of 2020. However, implementation has not been optimal in several areas, especially with difficult access. The purpose of this study was to observe the implementation of pharmaceutical service standard policies in Community Health Centers in the peripheral area of ​​Samarinda City, East Kalimantan. This study used a mixed method approach with data collection techniques through observation with questionnaire instruments, in-depth interviews, and document reviews. The results of the study showed that pharmaceutical preparation management activities had been carried out very well (94-100%) based on applicable standards. Meanwhile, the implementation of clinical pharmacy services showed variations in achievement among the health centres. Several activities such as prescription assessment and counselling have been optimal, but other indicators such as monitoring of drug side effects, evaluation of drug use, and inpatient visit activities have not been running optimally. In conclusion, the implementation of pharmaceutical services at the Health Centers in the peripheral area of ​​Samarinda City has mostly been following standard policies, especially in the aspect of managing pharmaceutical preparations and disposable medical materials. However, strengthening of clinical pharmacy services is still needed to optimize the role of pharmacists in comprehensive pharmaceutical services.